Kebijakan Pendidikan Inklusif Pada Sekolah Dasar: Implementasi, Hambatan, Dan Strategi - Nainggolan, Risnawati; Murniarti Erni (JPT : Jurnal Pendidikan Tematik, 2024)
Inclusive education is an educational policy aimed at ensuring that all students, including those with special needs, can learn together in regular school environments. This article examines the implementation of inclusive education policies at the elementary school level, focusing on aspects of implementation, the challenges encountered, and strategies to overcome those challenges. Through a review of literature from various scholarly sources, the article highlights that the implementation of inclusive education requires support and collaboration among the government, schools, and the community. The government provides financial assistance to schools that implement inclusive education. In addition, it conducts training and mentoring programs for school principals and teachers to enhance their understanding of inclusive education. Schools that provide inclusive education are expected to offer adequate facilities and infrastructure to accommodate students with special needs. The main challenges include limited resources, social stigma, and schools’ readiness. The strategies proposed in this article include developing adaptive curricula, providing accommodations in the learning process, and conducting continuous evaluation. This study contributes to practical insights for improving the effectiveness of inclusive education in Indonesia.